Suppressive Effects of Transient Receptor Potential Melastatin 8 Agonist on Epileptiform Discharges and Epileptic Seizures - Hiroshi Moriyama; Sadahiro Nomura; Sadahiro Nomura; Hirochika Imoto; Hirochika Imoto; Takao Inoue; Yuichi Fujiyama; Kohei Haji; Yuichi Maruta; Hideyuki Ishihara; Michiyasu Suzuki (Frontiers Media S.A., 2021)
Epilepsy is a relatively common condition, but more than 30% of patients have refractory epilepsy that is inadequately controlled by or is resistant to multiple drug treatments. Thus, new antiepileptic drugs based on newly identified mechanisms are required. A previous report revealed the suppressive effects of transient receptor potential melastatin 8 (TRPM8) activation on penicillin G-induced epileptiform discharges (EDs). However, it is unclear whether TRPM8 agonists suppress epileptic seizures or affect EDs or epileptic seizures in TRPM8 knockout (TRPM8KO) mice. We investigated the effects of TRPM8 agonist and lack of TRPM8 channels on EDs and epileptic seizures. Mice were injected with TRPM8 agonist 90 min after or 30 min before epilepsy-inducer injection, and electrocorticograms (ECoGs) were recorded under anesthesia, while behavior was monitored when awake. TRPM8 agonist suppressed EDs and epileptic seizures in wildtype (WT) mice, but not in TRPM8KO mice. In addition, TRPM8KO mice had a shorter firing latency of EDs, and EDs and epileptic seizures were deteriorated by the epilepsy inducer compared with those in WT mice, with the EDs being more easily propagated to the contralateral side. These findings suggest that TRPM8 activation in epileptic regions has anti-epileptic effects.